STRATEGI RELOKASI PEDAGANG KAKI LIMA (PKL) UNTUK PEMBENAHAN RUANG TERBUKA HIJAU (RTH) DI KOTA SUKABUMI - Maulida, Syifa (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2024)
The purpose of this study is to discuss the strategy for relocating street vendors to improve green open spaces in Sukabumi City so that the local government relocates. Based on this, researchers are encouraged to conduct research on how to relocate street vendors to improve green open spaces in Sukabumi City. This type of research is qualitative with a descriptive approach that uses data analysis techniques by conducting interviews, observations, and documentation by describing general events regarding the problem of street vendors in the city of Sukabumi. The results of this study indicate that the strategic management carried out by the Housing and Settlement Spatial Planning Office and Satpol PP has not fully run optimally, because the Housing and Settlement Spatial Planning Office is more focused on one side of the function while the Satpol PP enforces Regional Regulation No. 10 of 2013 regarding Arrangement and Empowerment of street vendors in Sukabumi City are still conducting guidance and routine patrols to street vendors who violate the rules.